Effect of biofeedback pelvic floor training on urodynamic study in children with detrusor sphincter dyssynergia - Mervat Sheta Elsawy; Haytham El Metwally Badawy; Mohamed Abdel Sattar Sharafeldeen; Waleed Dawood (Alexandria Journal of Medicine)
Introduction Detrusor sphincter dyssynergia (DSD) is the urodynamic description of bladder outlet obstruction from detrusor muscle contraction with concomitant involuntary urethral sphincter activation. DSD is associated with neurologic conditions such as spina bifida. It is associated with urinary incontinence (UI), nocturnal enuresis, urgency, intermittency, and recurrent urinary tract infections (UTIs).The Aim of this Study It aims to assess the efficacy of biofeedback (BF) for achieving perineal synergy and improving symptoms in thirty children with refractory DSD who failed to improve with medical treatment in the last 2 to 3 years.Material and Methods Thirty children (20 girls and 10 boys) aged 6–18 years (mean: 9.2 ± 2.2 yrs) with refractory DSD who failed to show improvement after 2–3 years of medical treatment with recurrent UTI and failure to emptying completely their bladder using urodynamic study. After patients understood the concept of BF pelvic floor training were regularly scheduled twice weekly for up to 3 months. Improvement was assessed using interview with parents after 3 months with measurement of manomeric pelvic floor muscles (PFMs) during straining and urodynamic study.Results Seven (23.3%) of the 30 children had daytime UI and 11 (36.7%) had nighttime incontinence. 4/30 (13.3%) children had increased urgency and 5 (16.7%) had straining intermittency and 3% (10%) had Dysuria. After 3 months of BF pelvic floor training 7/30 (23.3%) of children were fully responsive 100% decrease of symptoms, 14/30 (46%) responded more than 90% decrease of their symptoms, 7/30 (23.3%) of children responded partial decrease of symptoms and 2/30 (0 to 49%) decrease of symptoms to BF pelvic floor training.Conclusions BF pelvic floor training is an effective therapeutic option for children with refectory DSD. It improves symptoms of children with DSD with decreased UTIs through decreasing pressure of PFMs during urination.